NILAI-NILAI MORAL DALAM NASKAH AMANAT GALUNGGUNG UNTUK PENDIDIKAN KARAKTER - Wijayanti, Yeni (Universitas Galuh, 2018)
The purpose of this research is to obtain an overview of the moral values of Amanat Galunggung Manuscript that can be applied in character education. As is known, Amanat Galunggung Manuscript is a human product of the past which is still relevant for the present. Especially if you look at the phenomenon of moral decadence that occurs in society. The research method is used as a historical method consisting of heuristics, criticism, interpretation, and historiography. The results of this research indicate that the values contained in the Amanat Galunggung Manuscript include religious values, honesty, tolerance, hard work, the spirit of nationalism and love of the homeland, communicative, peaceful, and responsible.